Modeling Distribution Patterns of Colloidal Particles on Electrophoretic Deposition Demonstrated Using Kinetic Monte Carlo Simulation - Rahma wati; Leo Chau-Kuang Liau; Nurviana Nurviana (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2026)
Electrophoretic deposition (EPD) patterns of colloidal SiO2 particles (400 nm) in solution were analysed and demonstrated using the kinetic Monte Carlo (KMC) simulation method. The behaviour of the colloidal particles which formed electrical double layers in solution was described by the DLVO theory. The dynamic particle migrations of the EPD process were estimated by the KMC simulation to statistically determine the probable particle distribution based on thermodynamic theories. Results show that the particle distribution and deposition in solution were significantly influenced by the presence of the zeta potential value (η) in the solution, and applied voltage in the EPD system. The particles aggregated together in the solution with a small η value due to the strong Van der Waals attractive forces among the particles. If a large η value was adopted, all the particles moved away from central and scattered around the edges the system space because of the strong electrostatic (repulsive) forces among them. The external voltage applied to the EPD system in different η value can affect the formation of particle deposition pattern. The EPD pattern with little vacancy site can be fabricated using a small η value with a constant voltage operating condition. However, the vacancy sites of the EPD pattern became large by the on-off voltage operating scheme. The quality of the EPD films cannot be improved using this strategy.